Different Eggs Portions from Commercial Layers and Local Chickens Affected Differently, the Levels of Blood Lipids, and Abdominal and Liver Fat in Treated Wistar Rats - Mwangengwa, Lusekelo Msomba; Mgonja, Frida Richard (Journal of Biology and Life Science, 2024)
The presented study investigated whether egg portions from commercial layers and local chickens may have different effects on the levels of blood lipids and visceral fat in consumers using Wistar rats as an experimental model. Prepared egg portions included the whole egg (mixture of Egg white + yolk), Egg white and egg yolk. Then, 35 rats were randomized into seven groups (n = 5). Group 1 (control) received tap water. Groups 2, 3 and 4 received by gavaging 10mg/gBW of the commercial layer sourced whole egg, egg yolk and Egg white respectively. Groups 5, 6 and 7 consumed the same amount of similar egg portions from local chickens. Also, all groups were maintained on broiler mash and adlib water (without restriction). Treatment covered 28 days, then, rats were sacrificed after sedation in ether. Blood was collected to analyze blood lipids. The abdominal fat and Liver were dissected and weighed. Hepatic fat infiltration was assessed by histological examination. Rats eating the whole egg from either the commercial layer or local chickens had their abdominal fat and Liver’s weights increased significantly compared to the control. Also, rats eating the whole egg or only the egg yolk from either commercial layers or local chickens showed a significantly elevated serum TG, HDL-C and LDL-C compared to the control. Moreover, the effects caused by the commercial layer egg fractions exceeded significantly those caused by egg portions from local chickens. Moreover, the rats’ Liver histology indicated numerous fat-infiltrated, enlarged hepatocytes in rats that were orally gavaged by the whole egg or only the yolk from commercial layers. Also, regardless of the egg source, the egg white showed no significant effects on visceral fats and blood lipids of the treated rats. In conclusion, feeding the egg whites had no significant effect on the visceral fat and blood cholesterol of the treated rats. However, the whole egg or egg yolk from commercial layers exceeded significantly similar egg portions from local chickens in increasing the levels of viscera fat and blood cholesterols in the treated rats.